Respuesta :
Answer:
all of your answers are correct
1.) 64
2.) x= -5+4i and x= -5-4i
3.) (4x+3iy)(4x-3iy)
Answer:
1.
When we are completing squares, we need to divide by 2 the linear term and then find its square power, that's the term we need to add on both sides of the equality, as follows
[tex](\frac{16}{2})^{2} =(8)^{2}=64[/tex]
Basically, we need to add the number 64 both sides
[tex]x^{2} +16x+64=18+64[/tex]
2.
The given equation is
[tex]x^{2} +10x+41=0[/tex]
We need to apply the quadratic formula to solve this equation
[tex]x_{1,2} =\frac{-b(+-)\sqrt{b^{2}-4ac } }{2a}[/tex]
Where [tex]a=1[/tex], [tex]b=10[/tex] and [tex]c=41[/tex]. Replacing these values, we have
[tex]x_{1,2} =\frac{-10(+-)\sqrt{10^{2}-4(1)(41) } }{2(1)}\\x_{1,2} =\frac{-10(+-)\sqrt{100-164 } }{2}=\frac{-10(+-)\sqrt{-64} }{2}[/tex]
There we need to use complex number, to transform the subradical number in a positive number
[tex]x_{1,2}=\frac{-10(+-)\sqrt{64}i }{2}=\frac{-10(+-)8i}{2}\\ x_{1,2}=-5(+-)4i[/tex]
Therefore, the complex solutions are
[tex]x_{1}=-5+4i\\ x_{1}=-5-4i[/tex]
3.
The given expression is
[tex]16x^{2} +9y^{2}[/tex]
To solve this expression, remember that [tex]i=\sqrt{-1}[/tex]
First, we expresse both squares uniformly,
[tex]16x^{2} +9y^{2}=(4x)^{2}+(3y)^{2}[/tex]
But, we know that [tex]-(-1)=1[/tex], so
[tex](4x)^{2}+(3y)^{2}=(4x)^{2}-(-1)(3y)^{2}[/tex]
Then,
[tex](4x)^{2}-(-1)(3y)^{2}=(4x)^{2}-(3y)^{2}i^{2}[/tex], because [tex]i^{2}=-1[/tex]
Therefore, the expression with complex numbers is
[tex](4x)^{2}-(3iy)^{2}\\\therefore (4x+3iy)(4x-3iy)[/tex]